KONSEP DIRI WANITA KARIR DALAM KELUARGA (Studi Kasus pada Ibu Rumah Tangga yang Bekerja Penuh di Kota Palu) - Kariono, Siti Munipa (Social Humanity: Jurnal Ilmu Sosial dan Humaniora, 2018)
The purpose of this study was to determine the self-concept of career women and career women's activities in Palu City. Data collection techniques are carried out by observation, in-depth interviews and documentation. Informants in this study were 5 (five) housewives who also worked professionally and researched in Palu City. The results showed that the career concept of female career was seen in 3 (three) concepts of George Herbert Mead, namely mind, self, and society. Mind career women are formed from thoughts about the ideal concept of career women, they consider the ideal career woman is the synergy between career and the main task of being a mother and wife and from what they experience that being a career woman is not a mistake as long as she understands her goal for a career and can position himself when becoming a housewife and when working professionally. Then self is formed because the family background is also a career so that the impulse appears to be a career woman, besides that because of the encouragement of herself who likes to work and society is that the closest environment that is family is fully supportive and motivated, the social environment looking negative does not really affect the decisions of career women in carrying out their dual roles.